Technological Model Based on Artificial Intelligence (AI) for the Improvement and Optimization of Customer Service Experience through GPT - Orellana Vasquez, Mayly Chesca (2025)
The proposal focuses on the implementation of a personalized service platform that integrates and trains data using the GPT model (Generative Pre-trained Transformer) to improve customer satisfaction by responding to their requests accurately, promptly, and swiftly. The proposed methodology for the technological model integrates artificial intelligence (AI) and GPT technologies, allowing the loading of documents in different formats, such as PDF and Markdown documents, which are then analyzed using the aforementioned technologies to respond to customer requests precisely, enabling a more personalized and efficient interaction. For testing the technological model, a prototype was designed, from which the level of satisfaction of a sample of 50 customers was evaluated after interacting with the application and the traditional method. As a result, it was observed that customers experienced a satisfaction level of 59.4% when served traditionally, while with the technological model interaction, they recorded an average satisfaction of 92.6%. Therefore, the research concludes that the proposed technological model represents an opportunity to efficiently address customer service requests, providing a more effective and satisfactory service, which also implies the optimization of resources and costs for an organization.